People with Social Welfare Problem and Its Solving in Underdeveloped Region - Murdiyanto Murdiyanto (Balai Besar Litbang Pelayanan Kesejahteraan Sosial, 2014)
This research is done to get an objective information on social welfare problems and its solving in underdeveloped region. Research location ditermined purposively in Baramamase Village, Walenrang Underdistrict, Luwu Regency, South Celebes Province, under the consideration that the region has high prevalency of social problems among other regions. Data gathered through interview, observation, and documentary analysis. The result shows that social problems in Baramamase Village are unhabitable houses, poor families, flood victims natural disaster, economic and social vulnerable women, and neglected children. Initial problem solving that is done are maping and finalizing data, then followed by treatment. It can be concluded that social problems in Baramamase Village is caused by poverty factor. For the social problem solving, especially poverty in underdeveloped region that have not been adequatly covered by the program, it is recommeded that the program should be implemented comprehensively by the government, privat sector, individual, and group. The partisipation of those institution should refer to their respective competencies, so that no overlap policies among commited institutions happen in the implementation of the program.